Geophysical Investigation of the Impact of Solid Waste Dump on Subsurface Soil and Groundwater in Eneka, Rivers State Nigeria - NWANKWO, Cyril; OGORO, Mark (GeoScience Engineering, 2020)
The geophysical electrical method was used to investigate how the refuse dump in Eneka (Rivers State, Nigeria) affects the subsurface soil and groundwater within its environs. The research was carried out applying Wenner and Schlumberger array configurations of electrical resistivity techniques to image the subsurface resistivity within the area using ABEM SAS 300 Terrameter. A total of ten locations were investigated and the measured data across the profiles were processed using RES2DINV and ArcGIS 10.4 computer iterative software. The resulting inverse resistivity model isolated three resistivity zones (anomalously low, intermediate and high resistivity). The anomalously low resistivity zone was interpreted as contaminant leachate plumes and landfill gases from the dump area was observed to have travelled to depths of 14 m below the surface and over 30 m distance eastwards from the dump site, showing the tendency of farm land and crops pollution. However, the aquifer layer in the area estimated at the depth of 40 m may not have been contaminated. The spatial trend of almost all the resistivity values measured at equidistance reveals low value for lines 3 and 4 (which are farther away from the dump site) at the beginning and high value at the end and vice versa for lines 1 and 2. At the rate at which the leachate has infiltrated the subsurface the aquifer within the area is likely to be contaminated in the future if adequate measures are not taken. Keywords: Dump site; Electrical resistivity; Eneka; Groundwater; Leachate plume. DOI 10.35180/gse-2020-0037